Plant-derived compounds stimulate the decomposition of organic matter in arctic permafrost soils - Wild, Birgit; Gentsch, Norman; Čapek, Petr; Diáková, Kateřina; Alves, Ricardo J Eloy; Bárta, Jiři; Gittel, Antje; Hugelius, Gustaf; Knoltsch, Anna; Kuhry, Peter; Lashchinskiy, Nikolay; Mikutta, Robert; et al. (Scientific reports, 2016)
Arctic ecosystems are warming rapidly, which is expected to promote soil organic matter (SOM) decomposition. In addition to the direct warming effect, decomposition can also be indirectly stimulated via increased plant productivity and plant-soil C allocation, and this so called "priming effect" might significantly alter the ecosystem C balance. In this study, we provide first mechanistic insights into the susceptibility of SOM decomposition in arctic permafrost soils to priming. By comparing 119 soils from four locations across the Siberian Arctic that cover all horizons of active layer and upper permafrost, we found that an increased availability of plant-derived organic C particularly stimulated decomposition in subsoil horizons where most of the arctic soil carbon is located. Considering the 1,035 Pg of arctic soil carbon, such an additional stimulation of decomposition beyond the direct temperature effect can accelerate net ecosystem C losses, and amplify the positive feedback to global warming.